Governance Transformation in Indonesia’s Banking Sector: Regulatory Pressures and Institutional Dynamics in the Conversion of Bank Riau Kepri to Islamic Banking - Megawati, Devi; Khairunisa, Madona; Zulkifli, Zulkifli (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2025)
This study investigates the governance transformation underpinning the conversion of Bank Riau Kepri (BRK) into Bank Riau Kepri Syariah (BRK Syariah), focusing on the interplay between regulatory pressure, institutional dynamics, and strategic intent. Using a qualitative case study design, the analysis reveals that the conversion was driven by a combination of internal aspirations for regional economic leadership and external pressures, including regulatory encouragement and alignment with national Islamic finance roadmaps. While institutional support and political endorsement facilitated the conversion, challenges remain in harmonizing Sharia principles with operational realities, including staff capacity, legacy systems, and market adaptation. The study contributes to the growing discourse on conventional-to-Islamic bank conversion by highlighting how regulatory ecosystems, institutional inertia, and governance reform intersect in shaping the trajectory of Islamic banking transformation in Indonesia.  Keywords: Islamic banking transformation; governance reform; regulatory pressure; institutional adaptation; conventional-to-Islamic conversion; Bank Riau Kepri    Abstrak. Studi ini menelaah transformasi tata kelola yang mendasari proses konversi Bank Riau Kepri (BRK) menjadi Bank Riau Kepri Syariah (BRK Syariah), dengan menyoroti interaksi antara tekanan regulasi, dinamika kelembagaan, dan strategi institusional. Melalui pendekatan studi kasus kualitatif, temuan penelitian menunjukkan bahwa proses konversi dipicu oleh aspirasi internal untuk menjadi pemimpin ekonomi regional serta dorongan eksternal berupa dukungan regulatif dan sinkronisasi dengan peta jalan keuangan syariah nasional. Meskipun konversi difasilitasi oleh dukungan kelembagaan dan legitimasi politik, tantangan tetap muncul dalam menyelaraskan prinsip-prinsip syariah dengan praktik operasional, termasuk kapasitas SDM, sistem warisan, dan adaptasi pasar. Studi ini memperkaya wacana tentang konversi bank konvensional menjadi bank syariah dengan menyoroti bagaimana ekosistem regulatif, inersia kelembagaan, dan reformasi tata kelola membentuk arah transformasi perbankan syariah di Indonesia. Kata kunci: Transformasi perbankan syariah; reformasi tata kelola; tekanan regulasi; adaptasi kelembagaan; konversi bank; Bank Riau Kepri